1985
DOI: 10.1007/bf01212654
|View full text |Cite
|
Sign up to set email alerts
|

Study of a photo-induced lysozyme-riboflavin bond

Abstract: Irradiation of lysozyme in the presence of riboflavin results in the formation of a lysozyme-riboflavin adduct. Reduction and carboxymethylation of the four disulfide bonds as well as the chemical modification of the Tyr residues and the photochemical alteration of the His residue in lysozyme, do not affect the formation of the photo-induced lysozyme-riboflavin bond. When the lysozyme-riboflavin adduct was subjected to mild acid hydrolysis and ion exchange chromatography, the retention of a compound containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…The interaction between triplet riboflavin and crystallins together with the induction of protein crosslinking at low oxygen concentration has been demonstrated (37). The amino acids susceptible to Type‐I interaction are mainly Trp, Tyr and His (42,43). Formation of Trp–Trp (44) and Tyr–Tyr (45,46) crosslinks through radical mechanisms has been observed.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between triplet riboflavin and crystallins together with the induction of protein crosslinking at low oxygen concentration has been demonstrated (37). The amino acids susceptible to Type‐I interaction are mainly Trp, Tyr and His (42,43). Formation of Trp–Trp (44) and Tyr–Tyr (45,46) crosslinks through radical mechanisms has been observed.…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence emission remained constant in time even after the system was further exposed to the action of visible light. Once the free RF present in the irradiated BSA solution was eliminated from the medium by dialysis, it was found that the irradiated protein presented an absorption band in the region from 300 to 580 nm, which accounts for the establishment of a photochemical binding between RF and BSA (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…Noteworthy, in the same region the protein matrix was less immunoreactive than toward the central region of the lens. (20). This kind of compound may also be obtained through the energy transfer from enzymatically generated excited species to R F (2 1,22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between LZ and RF upon illumination generates LZ-RF adduct and photooxidation of LZ might be sensitized by RF bound to the protein and in solution (Silva & Gaule, 1977). Ferrer & Silva (1984) noted that reduction and carboxymethylation of the four disulfide bonds as well as the chemical modification of the Tyr residues and the photochemical alteration of the His residue in lysozyme, do not affect the formation of the photo-induced LZ-RF bond. However, 3 RF * can be quenched by O 2 via energy transfer to form 1 O 2 which is a strong oxidizing agent and can induce further oxidation of protein resulting in more efficient photooxidation.…”
Section: Discussionmentioning
confidence: 99%